(3CRgGQ GdHSJGf aj WHbGJ GdCYjGfs - (3CMeO Hf eMeO Hf GdegOj, GHf nYpLjHI, GdMSfj GdCfLQj,J (B1224 (3g` s
(3ChdgG (B:s
(3hHYO bO ENJUQJ aj gPG GdeLehY fHPI UGdMI ef eTGgjQ CYjGf ePgH eGdc QMeI Gddg s
(3BNQgG (B:s
(3hUahI ef EfJTQ ddjaQGfj, hGdfRgI ddbGOQi s
(3cKjQ ef UaMGJgG aGSO GdJUhjQ dGjbQCs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B245 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B163s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B25 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(286 (3c(B) s
Keywords: (3GdJGQjNs